2001
DOI: 10.1021/es010557u
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of SO2on Sewage Sludge-Derived Materials

Abstract: Sewage sludge-derived materials carbonized at temperatures between 400 and 950 degrees C were used for adsorption of sulfur dioxide from dry and moist air. The materials were characterized using sorption of nitrogen and thermal analysis. The sulfur dioxide capacity was measured according to a laboratory-developed breakthrough test. It was found that the capacity of the adsorbents increases with increasing temperature of carbonization. It is likely that during carbonization at high temperatures such catalytic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 29 publications
(83 reference statements)
0
49
0
1
Order By: Relevance
“…For the unexposed samples, the weight loss between 250 • C and 450 • C represents decomposition of inorganic matter and/or decomposition of oxygen-containing functional groups [33]. After exposure to SO 2 at dry conditions, the main peak between 350 • C and 550 • C corresponds to dehydroxylation of surface hydroxyl groups and/or volatilization of sulfates that are formed by reaction of inorganic components or metal oxides of the adsorbents with adsorbed sulfur dioxide [34,35]. Furthermore, the Fourier-transform infrared spectra are also used to illustrate the adsorption mechanism.…”
Section: So 2 Adsorption Performance Studiesmentioning
confidence: 99%
“…For the unexposed samples, the weight loss between 250 • C and 450 • C represents decomposition of inorganic matter and/or decomposition of oxygen-containing functional groups [33]. After exposure to SO 2 at dry conditions, the main peak between 350 • C and 550 • C corresponds to dehydroxylation of surface hydroxyl groups and/or volatilization of sulfates that are formed by reaction of inorganic components or metal oxides of the adsorbents with adsorbed sulfur dioxide [34,35]. Furthermore, the Fourier-transform infrared spectra are also used to illustrate the adsorption mechanism.…”
Section: So 2 Adsorption Performance Studiesmentioning
confidence: 99%
“…High specific surface area (up to 880 m 2 /g) and pore volume (up to 0.46 cm 3 /g) along with the presence of metal oxides in the sorbent composition provide quite a high dynamic capacity for sulfur dioxide (up to 50 mg/g). Investigation of sulfur dioxide adsorption (0.3% in air) at room temperature revealed that humidification of the gas stream (up to a relative humidity of 80%) results in a more efficient adsorption of SO 2 : under such conditions, dynamic capacity of the sorbent was approximately two times higher as compared to the dry gas [12]. The beneficial effect of water on SO 2 adsorption is attributed to the formation of surface hydroxyl groups in metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…(Lelieveld and Heintzenberg, 1992 ; McDonald-Buller et al, 2016 ). Till now, to remove SO 2 released from the burning of fossil fuels, several effective methods has been developed (Srinivasan and Grutzeck, 1999 ; Bashikova et al, 2001 ; Xia et al, 2011 ; Kaplan et al, 2013 ; Yang et al, 2013 ). Among these technologies, Wet Flue Gas Desulfurization (WFGD) has been one of the state-of-the-art technologies for SO 2 removal with high efficiency, simple equipment and obtaining multi-useful byproducts (Yang et al, 2012 ; Lu et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%